2020
DOI: 10.1186/s12888-020-02587-z
|View full text |Cite
|
Sign up to set email alerts
|

Self-harm with suicidal and non-suicidal intent in young people in sub-Saharan Africa: a systematic review

Abstract: Background Self-harm, whether attributed to suicidal or non-suicidal motives, is associated with several poor outcomes in young people, including eventual suicide. Much of our understanding of self-harm in young people is based on literature from Europe (particularly, the UK), North America, and Australia. We aimed to synthesise the available evidence on prevalence, the commonly reported self-harm methods, correlates, risk and protective factors, and reasons for self-harm, in adolescents (aged 10–25 years) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
79
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 89 publications
11
79
1
Order By: Relevance
“…Evidence from LMICs suggests a strong positive association between marijuana use and attempted suicide among young people. 13 14 Our study has extended this evidence by indicating that marijuana use has a strong positive association with repeated attempted suicide among SHS students in Ghana. After controlling for confounding factors associated with marijuana use and adjusting for demographic covariates, this study found marijuana use to be significantly associated with repeated attempted suicide among SHS students in Ghana.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Evidence from LMICs suggests a strong positive association between marijuana use and attempted suicide among young people. 13 14 Our study has extended this evidence by indicating that marijuana use has a strong positive association with repeated attempted suicide among SHS students in Ghana. After controlling for confounding factors associated with marijuana use and adjusting for demographic covariates, this study found marijuana use to be significantly associated with repeated attempted suicide among SHS students in Ghana.…”
Section: Discussionsupporting
confidence: 68%
“…Thus, recent significant research efforts from low-income and middle-income countries (LMICs) have focused on examining the factors associated with attempted suicide among young people. 13 A recent study conducted by Carvalho and colleagues suggested a strong association between cannabis use and suicide attempts in adolescents living in LMICs. 14 However, as can be said of Ghana, whereas emerging evidence has underscored the key factors associated with marijuana use 6 and those related to the onset of attempted suicide among in-school adolescents, 3 15 there is a paucity of published studies providing evidence on the association between marijuana use and the repetition of attempted suicide among in-school adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…In studies conducted in the United States and Southeast Asian countries, female suicidal ideation ranged from 15.1%-23.4% ( 12 - 13 , 23 ), suicidal planning was 19.4%, and suicidal attempts were between 9.1% and 11.6% during the past 12 months ( 13 , 23 ). In a study conducted in 18 sub-Saharan African countries the median estimate of 12-month prevalence of self-harm was 16.9% in adolescents and adults (aged 10-25 years) ( 27 ). Among males, the presence of suicidal ideation, planning, and attempts were 10.7%, 8.6%, and 9.3%, respectively, during the past 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…of recent regional systematic reviews and meta-analyses indicates that compared to other low-and middleincome regions of the world, the 12-month prevalence estimates of suicidal ideation (20.4, 95% confidence interval [CI] = 17.3, 23.6), and suicidal planning (23.7,95%CI = 19.1,28.3) are higher among school-going adolescents in sub-Saharan Africa [10,11], while the pooled 12-month prevalence estimates of suicidal attempt among school-going adolescents in sub-Saharan Africa (19.3,95%CI = 14.2,24.4) is comparable to what is reported in other LAMICs within the Western Pacific region (20.5, 95%CI = 14.3, 26.7) [11]. The most recent systematic review of primary studies involving school-going, household and 'out-of-school' adolescents in sub-Saharan Africa has reported a comparable pooled 12-month prevalence estimates of suicidal attempt (median = 17.1%, interquartile range [IQR] = 11.5-25.6%) [12]. In Western sub-Saharan Africa, where Liberia is located, the pooled 12month prevalence estimates of suicidal attempt is relatively higher (Median = 24.3%, IQR = 16.9-27.9) [12].…”
mentioning
confidence: 89%